Polish corporations against foreign corporations in the age of globalization - Sala, Stanisław (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2006)
This article presents the role and the importance of Polish Transnational Corporations (TC) to global economy. Dynamic development of TC can be observed since the beginning of 70s of the 20thcentury. Nowadays TC have huge economic power which generates large profits. Many times incomes of TC are bigger than the value of GDP of less developed countries. Activity of TC is very controversial. On the one hand, present TC should be treated as an answer to qualitative changes which have taken place mainly in the sphere of telecommunication and means of transport, on the other hand, they are the motive power of these changes.Polish corporations are very small in comparison with the foreign ones. We have noticed a great disproportion of worth in comparison with corporations which are on the list of the global 1000 or 2000 biggest-worth corporations on the rising market. If Polish corporations want to catch up with the foreign ones, they must considerably increase the speed of their development